Pengaruh Model Tutor Sebaya Dan Motivasi Belajar Terhadap Pemahaman Konsep Keliling Lingkaran Siswa Kelas VI SD - Komariah, Neng; Kusumastuti, Mimin Nurjhani; Rosita, Tita (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The aim of this study is to analyze the influence of student peer-to-peer tutoring model and the level of learning motivation concerning the comprehension of the concept of circle circumference among the sixth-grade students. This study employs a quasi-experimental research design, specifically incorporating pre-test and pos-test assessments. The study's population consists of 107 students, with a sample size of 72 students selected through the utilization of a cluster random sampling technique. The study's instrument uses a form of questionnare and tests. The data analysis for this study involved the utilization of two-way-ANOVA using SPSS 23.0 software for Windows. The conclusions are; (1) A notable influence exists when employing the peer-to-peer tutoring model in enhancing students' comprehension of circle circumferences among sixth-grade students. (2) A distinct impact emerges from students' learning motivation on their grasp of circle circumference comprehension in the sixth-grade. (3) Significant influences are discerned from both the implementation of the peer-to-peer tutoring model and the level of learning motivation, collectively affecting the comprehension of circle circumference among sixth-grade students.